Diverging Destinies? A Long-term Outlook into Women’s Work and Gender Roles in Italy and Spain - Sánchez Mira, Núria; Camilla Gaiaschi; Valeria Insarauto; Joan M. Verd (My University, 2024)
This article analyses how social and economic transformations over the last two decades have shaped women’s position in the work and family spheres in Italy and Spain, two countries often clustered together with other Southern European countries and yet exhibiting distinct features. Taking a long-term outlook, we discuss patterns of change of labour market indicators and gender-role attitudes during periods of economic growth, recession and recovery, to identify the implications of such changes for models of female socio-economic integration and gender equality issues in both countries. We show that the divergent trends have situated the two countries in significantly different positions. While Italy seems to be on a trajectory of continuity, with no significant change in female labour market integration, Spain shows a fundamental path-departure from the distinctive characteristics of the Southern model, with the 2008 economic downturn acting as a catalyst for change regarding women’s work and family roles.
Keywords: Female activity; Part-time work; Gender-role attitudes; Southern Europe; gender inequalities